Equilibrium effects on the structure of island divertor and its impact on the divertor heat flux distribution in Wendelstein 7-X. (1st October 2022) - Zhou, S.; Liang, Y.; Knieps, A.; Suzuki, Y.; Geiger, J.; Dinklage, A.; Langenberg, A.; Pasch, E.; Jakubowski, M.; Pablant, N.; Wang, N.C.; Drews, P.; et al.
Abstract: To support the planning of high-performance long-pulse plasma operation for W7-X, the role of equilibrium effects for the structure of island divertor and its profound impacts on the divertor heat flux distribution have been investigated. Finite-beta full-field three-dimensional equilibria for the four most important configurations of W7-X ('standard', 'high-mirror', 'high-iota' and 'low-iota') were obtained with the HINT code. Equilibrium calculations show a strong dependence of the edge stochastization on the magnetic configurations. Parameterization to estimate equilibrium effects on edge stochastization and plasma shape was attempted for individual functions. The results indicate that a more stochastic boundary can be attained with increasing plasma beta, except for the low-iota configuration. According to fully diffusive heat-load estimations, it turns out that equilibrium effects are beneficial for spreading the heat flux on the divertor target. The interactions of the beta effects with effects driven by the toroidal plasma current are also analyzed for the standard configuration. Infrared camera measurements confirm the predictions concerning global heat load distributions.